Theological Questions - Hanneken, Todd (Open textbook library., 2022)
Theological Questions is an Open Educational Resource (free textbook) that originates from St. Mary’s University in San Antonio and was created with funding form the Atla OER Grant Program. This open textbook was used at St. Mary's in the first of two required core theology courses. It is designed to give a broad historical overview of theological questions from the perspective of the Catholic tradition. It seeks to represent fairly a variety of questions and answers within and beyond the Catholic tradition. This OER is a foundation for other teachers of introductory courses in theology who may wish to adapt it for their purposes.